208 Cardioprotection by the mitochondria-targeted superoxide generator mitoparaquat in a murine model of acute myocardial ischaemia reperfusion injury. (5th June 2017) - Mulvey, John; Logan, Angela; Arndt, Sabine; Pell, Victoria; Caldwell, Stuart; Hartley, Richard; Murphy, Michael; Krieg, Thomas
Abstract : Introduction: Myocardial infarction is a major cause of death and disease worldwide. Mitochondrial reactive oxygen species (ROS) are known to play a central role in the tissue damage caused by ischaemia-reperfusion injury (IRI), yet the use of antioxidant supplements in large scale clinical trials has been shown to have no beneficial effect and indeed some studies have suggested that the addition of exogenous ROS may decrease infarct size. This suggests that mitochondria may exhibit a biphasic response to ROS, termed mitohormesis, characterised by beneficial effects at low doses and detrimental effects at high doses. To investigate this phenomenon, a tool is required to precisely titrate mitochondrial ROS. MitoParaquat is a novel mitochondria-targeted molecule that redox cycles at complex I to produce superoxide, closely mimicking the production of superoxide as the proximal ROS species in vivo . Here it is used to investigate the role of ROS in protection against acute myocardial IRI. Methods: Male C57BL6/J mice aged 8–10 weeks were administered MitoParaquat or vehicle only control by intravenous injection 15 min before the induction of 30 min myocardial ischaemia by ligation of the left anterior descending coronary artery. After 2 hours of reperfusion, infarct size was determined by tripheyltetrazolium chloride staining. Results: MitoParaquat decreased infarct size relative to vehicle only control (42.3±4.3%) at doses of 1 nmol (30.0±4.0%), 100 pmol (22.7±2.3%), and 10 pmol (24.2±2.0%). At 1 pmol, no significant difference from vehicle only control was observed (41.5±8.6%), and at 5 nmol it was found to be lethal. There was no significant difference in the area at risk between any groups. Conclusions: First and foremost, the generation of low doses of exogenous ROS by MitoParaquat is shown to be protective against acute myocardial IRI in vivo . MitoParaquat is shown to exhibit a hormetic dose response curve, with protection conferred only in an intermediate dose range with high doses found to be lethal and infarcts from low dose not significantly different from control. Further work is required to determine the mechanism by which this cardioprotection occurs.